The importance of sharing clinical information: case report of an adverse reaction (Portuguese Journal of Family Medicine and General Practice, 2018)
Introduction: Although not very consensual, antiemetic therapy is widely used in clinical practice in order to minimize dehydration and reduce the need of intravenous fluid therapy. The choice of antiemetic drug is extremely important given the incidence of adverse reactions, which may reach 25% in pediatric age.Case description: A 12-year-old young boy was admitted in the emergency department of a private hospital with complaints of headache, fever and an episode of vomiting. Intravenous paracetamol and metoclopramide were administered, with subsequent improvement of the symptoms. However, sometime later, the patient resumed a severe frontal headache and psychomotor agitation, which led to his transfer to the emergency department of the National Health System. At admission, the patient was very anxious, agitated and uncomfortable. At the beginning of the physical examination, he began to exhibit dystonic movements that made communication difficult and rendered the physical examination impossible to perform, but he never lost consciousness. An extrapyramidal reaction to metoclopramide was suspected and intravenous biperiden was administered, with complete reversal of the clinical presentation.Comment: Although uncommon, acute dystonic reactions may occur within the therapeutic dose of metoclopramide. Family doctors attend patients of all ages; therefore, it is important to keep in mind the possible adverse effects of this medication, as well as to record and transmit information regarding the therapeutic actions performed, which were fundamental in this case. In pediatric age, the administration of others drugs with well-established safety such as ondansetron and domperidone is advised.
Keywords: Extrapyramidal; Metoclopramide; Pediatric; Antiemetics.